0 votes

X²=3x

Therefore,

X²-3x=0

By moving all factors to the left.

Now for each factor being equal to zero.

1. X²=0

Square becomes square root when crossing the equality sign to make X the subject of formula.

X=√0

X=0

2. -3x=0

X=3

By making X the subject of formula.

When the negative sign crosses the equality sign, it becomes positive.

So x=0,3

This reminds me so much about solving problems back in secondary school. I didn't like solving problems at all. I was just an average student when it came to that. I never enjoyed it and I only read to pass. I wouldn't even practice them until it was time for examination.

0 votes

What you are asking are the "roots" of the equation x^{2} = 3x. Remember that the equation that will allow us to get the root/s is the quadratic equation given by ax^{2} + bx + c = 0.

In this case, you need to rewrite the equation from x^{2} = 3x by moving all terms to the left. This will then give you the form *x ^{2} -3x = 0*, which will allow us to identify

**a** = 1

**b** = -3

**c** = 0

We now substitute this to the quadratic formula:

x= [−b±√b^{2}−4ac]/2a

Substituting the values will give you this:

x= [−(-3)±√(-3)^{2}−4(1)(0)]/2(1)

x= [3±√9]/2

x= [3±3]/2

__First root:__

x= [3+3]/2 = 6/2 = 3

__Second root:__

x= [3-3]/2 = 0

**Hence, the values of x or the roots of the equation are 3 and 0.**

0 votes

x^2 =3x

re setting the equation

x^2 -3x =0

factorizing left side

x (x-3) =0

we have two factors on left side x and x-3 each must be zero

so x=0 first factor

and x-3 =0 second factor

or x=3

we find two answers x=0 and x=3

re setting the equation

x^2 -3x =0

factorizing left side

x (x-3) =0

we have two factors on left side x and x-3 each must be zero

so x=0 first factor

and x-3 =0 second factor

or x=3

we find two answers x=0 and x=3

0 votes

X^2 =3X

X^2 - 3X=0

X(X-3)=0

Either

X=0,

Or

X-3=0

X=3

We can also solve by making quadratic equation ax^2 +bx+c=0

And solve for the quadratic equation

Here c is zero

X^2 - 3X=0

X(X-3)=0

Either

X=0,

Or

X-3=0

X=3

We can also solve by making quadratic equation ax^2 +bx+c=0

And solve for the quadratic equation

Here c is zero

0 votes

We are given:

x^2 = 3x

By taking 3x to the left-hand side of the equation, we have:

x^2 - 3x = 0

Now:

We can see that in the given equation, two terms are there. One is x and another is 3x.

Among these two terms, x is a common factor.

By taking x as a common from both terms, we have:

x(x-3) = 0

So:

x = 0

And:

x - 3 = 0

=> x = 3

Hence:

The values of x are 0 and 3

4,086 questions

13,758 answers

5,253 comments

4,031 users